The burning bridge - Flanagan, John (John Anthony) (Flanagan, John (John Anthony). Ranger's apprentice, 2006)
Will is forced to overcome his fear of Wargals, the foot soldiers of rebel warlord Morgarath, as Araluen's army prepares to battle Morgarath's forces.